Pengaruh Kepemimpinan Transaksional Dan Kepemimpinan Transformasional Terhadap Kepuasan Kerja Pegawai Universitas Lancang Kuning - sr, nurmansyah (Komunitas Manajemen Kompetitif, 2016)
This research was conducted at Lancang Kuning University . The purpose of the study to know and analyze the effect of transactional and transformational leadership style to Job Satisfaction empolyees in Unilak. This study is useful to share ideas in the context of human resource development, so the employees may optimally serve students by possessing Job Satisfaction Employees and effective leadership style implementation. Variables used were Job Satisfaction employees as dependent and transactional and transformational leadership style used as independent. Population were 123 employees of Unilak. Samples determined by using Slovin formulation that consisted of 56 employees who were selected by using convenience sampling method. Hypothesis test were conducted by using multiple linier regression analysis that assisted with SPSS 22 for windows. Transactional and transformational leadership positively and significantly influenced the Job satisfaction employees among employees of Unilak, but partially Transformational leadership not significant influence to job satisfaction employees. It means that the Job Satisfaction employees’ were determined by how effective leaders can implement the appropriate leadership style. Therefore, it is recommended to Unilak leaders and management to properly analyze the situation and condition, so that leaders will know the proper time about when the transactional or transformational should be implemented. Keywords: Transactional Leadership, Transformational Leadership, Job satisfaction Employees